Dinamika Pembangunan Ekonomi Di Madura Pada Era Kebiasaan Baru Covid-19; Tantangan dan Peluangnya - Abd Hannan (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2021)
This study examines the challenges and opportunities for development in Madura amid the adoption of a new habit era due to the global pandemic, Covid-19. There are three main problems examined in this study; Econimi development in Madura, the era of new habits, and Covid-19. By using qualitative research and analysis based on the sociological theory of development, this study finds a number of findings; first, the dynamics of development in Madura in the midst of the adoption of a new habit era in general experienced quite serious upheavals or shocks, especially in the economic development sector. Second, the opportunities for strengthening Madura development in the midst of the new custom era are relatively open. This is influenced by the geographical condition of Madura as an archipelago which has abundant natural-social wealth, especially those originating from the maritime sector. Empowerment and utilization of natural resources, especially those based on local wisdom, can become a strategy in the midst of turbulent national-global economic chains; Third, to maximize these efforts, it is necessary to have collaboration and synergy with related parties, especially the government. In addition to ensuring the implementation of health protocols, it is equally important to ensure the financial power of the community. Providing stimulus packages, both fiscal and non-fiscal, so that later it can push the wheels of the regional economy. This is at the same time the biggest challenge, how to ensure that the distribution of the stimulus package is carried out in a measured, fast, and on target, as well as touching on fundamental sectors. (Studi ini mengkaji tantangan dan peluang pembangunan ekonomi di Madura di tengah diterapkannya era kebiasaan baru akibat pandemi global, Covid-19. Terdapat tiga permasalahan pokok yang dikaji dalam penelitian ini; pembangunan Madura, era kebiasaan baru, dan Covid-19. Dengan mempergunakan jenis penelitian kualitatif dan analisa berdasarkan teori sosiologi pembangunan, kajian ini mendapati sejumlah temuan; pertama, dinamika pembangunan di Madura di tengah penerapan era kebiasaan baru secara umum mengalami gejolak atau guncangan cukup serius, khususnya di sektor pembangunan ekonomi. Kedua, peluang penguatan pembangunan di Madura di tengah diberlakukannya era kebiasaan baru relatif terbuka. Demikian dipengaruhi oleh kondisi geografis Madura sebagai daerah kepulauan yang mempunyai kekayaan alam-sosial cukup melimpah, terutama yang bersumber dari sektor kemaritiman. Pemberdaayaan dan pemanfaatan kekayaan alam khususnya yang berbasis kearifan lokal dapat menjadi strategi di tengah gejolak rantai ekonomi nasional-global yang tidak menentu; Ketiga, untuk memaksimalkan upaya tersebut, perlu adanya kolaborasi dan sinergitas antara pemerintah dan elemen masyarakat. Selain memastikan jalannya protokol kesehatan, pun tak kalah pentingnya adalah memastikan daya finansial masyarakat. Memberi paket stimulus baik fiskal maupun nonfiskal, sehingga nantinya dapat mendorong roda perekonomian daerah. Ini sekaligus menjadi tantangan terbesar, bagaimana memastikan distribusi paket stimulus tersebut dilakukan secara terukur, cepat, dan tepat sasaran, serta menyentuh sektor-sektor fundamental.)